Interpretation of Eccentricity of an Enameled Wire by Capacitance Measurements - Sonia Ait-Amar; Abdoulay Koita; Gabriel Vélu (Energies, 2022)
There are systems dedicated to measuring the eccentricity of enameled wires based on optical and electromagnetic phenomena. However, these methods are limited by the nature of the insulation and the conductor. The proposed solution consists of checking the wire eccentricity by an electrical measurement. Since it is a conductor on which an insulator is placed, the idea consists of forming a capacitor and measuring its capacitance in order to deduce the insulation thickness.